Pemberdayaan Ekonomi Desa Melalui Digitalisasi Badan Usaha Milik Desa - Rina Dian Rahmawati; Lailatul Mathoriyah; M.Dzikrul Hakim; Laylatul Desia Rohmawati; Hilda Nur Roudhotul Jannah; Lubis Kurniawan (Journal of Social Empowerment, 2022)
Competence in the field of information technology is an important thing needed in this current era, where collaboration between academia and industry is needed to accelerate the realization of Industry 4.0 which is expected to have a negative impact on the economy, especially for developing countries with relatively high income levels. The Industrial Revolution also gave birth to a technology-based economy, which is commonly referred to as economic digitization. The development of village digitization is very useful and beneficial to boost the regional economy. The adoption of digital systems is said to be able to increase the potential of micro, small and medium enterprises (MSMEs). BUMDes is a legal entity created by the village for the purpose of running a business, using assets, investing in development and productivity, providing services and providing other types of businesses for the benefit of the village. BUMDes was born as a new approach to improve the village economy based on the local needs and potential of each region. The purpose of this research is to empower the village economy by utilizing information and communication technology through Village Owned Enterprises (BUMDes). In this study, combining the R&D (Research and Development) method, which is a research method used to produce certain products, and testing the effectiveness of these products with the Participatory Action Research (PAR) method. The results of this study are the optimal use of Facebook Marketplace in the efforts of BUMDes partners and MSME activists to promote products online and increase knowledge that there are several other social media that can be used as promotional media besides Facebook. Building interest in people who have businesses and MSME activists in training on the use of technology to facilitate promotion.